Transformatization of accounting in the digitalization of the economy - Ivanova, T.N. (Ways to Improve Construction Efficiency, 2022)
The existing system of accounting in enterprises needs to be transformed in the context of globalization of the economy and its digitalization. Analysis of existing approaches to the training of accountants and current requirements of stakeholders to it indicate a lack of practical readiness of graduates for modern challenges of the digital economy. The purpose of the study is to determine changes in the accounting system and their impact on enterprise management and training of accounting professionals in terms of its digitalization in the economy and the world. The article considers the existing approaches to the accounting system in enterprises and the role of the accountant. The main advantages of accounting in the digital economy are identified, the need for its transformation in today’s conditions is proved, as well as the challenges facing future accountants in the digitalization. The main trends in the development of the accounting system in the digital economy necessitate advanced skills of accountants, which are information technology, analysis of large data, communication skills and opportunities to promote accounting services as a business on social networks. Approaches to the content of the profession of "accountant" requires a qualitative transformation in the context of widespread use in accounting processes of digital technologies. In the context of digitalization of accounting due to the wider capabilities of the system, the accountant-analyst can give useful advice to the head of the company and justify the effectiveness of important management decisions. With the help of information technology used by modern accounting system, the accountant has more time to quickly and efficiently perform functional tasks, as well as data analysis and financial reporting. Owners (managers), receiving analytical, accurate and timely information, can focus on strategic goals and solving complex problems. It is proposed to include in educational programs in the field of specialties competencies that will promote the competitiveness of future and existing accountants in the digital economy.